DOMPET DIGITAL: BERAGAM PROGRAM PROMOSI DAN PENGARUHNYA TERHADAP PEMBELIAN SECARA IMPULSIF - Sadana Devica (Jurnal Bisnis Terapan, 2022)
This study aims to determine the effect of promotional programs on impulse buying. This research was conducted on 200 students. Data were processed using confirmatory factor analysis (CFA) and regression analysis. There are four indicators of the promotion program studied, including 1) promotions in the form of cashback, reward points or discounts offered by digital wallets are very profitable; 2) promotions obtained in the form of cashback or reward points will save on purchase transactions; 3) payment transactions using digital wallets are more profitable than transactions using cash or non-cash (debit/credit cards); and 4) selecting tenants/retailers/shops/e-commerce/online transportation that cooperates with digital wallet platforms to benefit from the promotional programs offered which have proven to have a positive and significant effect on impulse purchases. The impulsive buying behavior shown by digital wallet users includes 1) using digital wallets as a means of payment transactions because they are interested in the promotional programs offered and 2) often making purchases without prior planning because they are interested in promotional programs offered by digital wallets found in various tenant/retail/store/e-commerce/online transportation.